The German Model of Industrial Relations: (Where) Does It Still Exist? - Michael Oberfichtner; Claus Schnabel (Institute of Labor Economics (IZA), 2017)
Using data from the representative IAB Establishment Panel, this paper charts changes in the two main pillars of the German IR model over the last 20 years. It shows that collective bargaining coverage and worker representation via works councils have substantially fallen outside the public sector. Less formalized and weaker institutions such as voluntary orientation of uncovered firms towards sectoral agreements and alternative forms of employee representation at the workplace have partly attenuated the overall erosion in coverage. Multivariate analyses indicate that the traditional German IR model (with both collective agreements and works council presence) is more likely to be found in larger and older establishments, and it is less likely in establishments managed by the owner, in single and foreign-owned establishments, in individually-owned firms or partnerships, and in exporting establishments. In contrast, more than 60 percent of German establishments did not exhibit bargaining coverage or orientation or any kind of worker representation in 2015. Such a complete absence of the main institutional features of the German IR model is predominantly found in small and medium-sized establishments, in particular in the service sector and in eastern Germany, and its extent is increasing dramatically.
Keywords: J50; J52; J53; 330; collective bargaining; bargaining coverage; works council; worker participation; industrial relations; Germany